Microplastic in The Bali Strait : Comparison of Two Sampling Methods - Defri Yona; Zefanya Nandaningtyas; Bernads Daniel Marolop Siagian; Syarifah Hikmah Julinda Sari; Agung Yunanto; Feni Iranawati; Mochamad Arif Zainul Fuad; Junika Chintia Ayu Putri; Mela Dita Maharani (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
Two methods of microplastics sampling in the Bali Strait, manta net (250 µm mesh size) and plankton net (20 µm mesh size), were compared. The difference in the mesh sizes could result in the difference of the microplastics found. Water samples from both sampling tools were analyzed with filtration and all organic materials were removed using Hydrogen Peroxide.  Natrium chloride (NaCl) was used to further separate microplastics and organic materials based on its density. The result identified three types of microplastics found in Bali Strait: fibers, films and fragments with total abundances of microplastics were 32.48 x 102 particles.m-3 and 16.33 x 102 particles.m-3using manta net and plankton net, respectively. These results indicated that the numbers of microplastics per cubic metres was higher using manta net sampling tool compared to plankton net. This may likely caused by the smaller size of the mesh used and also the sampling area covered using manta net.